(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This article discusses the political and economic relations between the Khiva Khanate and the Russian states in the first quarter of the 19th century. Information is provided on the diplomatic relations of the two states. Comments are made on the exchange of ambassadors and the goals set for the ambassadors.